2015
DOI: 10.1002/lt.24134
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of portal vein thrombosis in patients with cirrhosis due to nonalcoholic steatohepatitis

Abstract: Portal vein thrombosis (PVT) is a common complication of cirrhosis sometimes implicated in hepatic decompensation. There are no consistent epidemiologic data to suggest an increased risk of thrombotic complications in nonalcoholic steatohepatitis (NASH); however, research suggests an increased risk of thrombosis. Our aim was to examine the independent association between NASH cirrhosis and PVT in patients who underwent liver transplantation (LT) in a cross-sectional study. Data on all LTs occurring in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 29 publications
8
114
2
Order By: Relevance
“…The other interesting finding of our study was the identification of cryptogenic‐NASH cirrhosis as a risk factor for PVT, independent of other risk factors including DM. This is in concordance with two other previous studies showing NASH as a risk factor for PVT in patients with cirrhosis . The precise underlying mechanism, however, is not evident.…”
Section: Discussionsupporting
confidence: 91%
“…The other interesting finding of our study was the identification of cryptogenic‐NASH cirrhosis as a risk factor for PVT, independent of other risk factors including DM. This is in concordance with two other previous studies showing NASH as a risk factor for PVT in patients with cirrhosis . The precise underlying mechanism, however, is not evident.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is important because PVT is a common finding in patients with cirrhosis [4,6,19] and one that significantly impairs quality of life and post-LT outcomes [7][8][9] . Several risk factors have been suggested to increase the risk of PVT in patients awaiting liver transplantation, including non-alcoholic steatohepatitis [20] . The risk of hepatic decompensation with ascites for patients with cirrhosis was also significantly greater in the presence of PVT.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the relationship of the etiology of cirrhosis with the risk of PVT, a nationwide US survey enrolling, overall, 33,368 patients who underwent liver transplantation reported that NASH cirrhosis was the strongest risk factor independently associated with PVT [229]. These data attest that NASH is a prothrombotic state and suggest that PVT prevention may be particularly indicated in this population.…”
Section: Prevention Of Portal Vein Thrombosismentioning
confidence: 98%